Organic NIR-II molecule with long blood half-life for in vivo dynamic vascular imaging - Li, Benhao; Zhao, Mengyao; Feng, Lishuai; Dou, Chaoran; Ding, Suwan; Zhou, Gang; Lu, Lingfei; Zhang, Hongxin; Chen, Feiya; Li, Xiaomin; Li, Guangfeng; Zhao, Shichang; et al. (Nature communications, 2020)
Real-time monitoring of vessel dysfunction is of great significance in preclinical research. Optical bioimaging in the second near-infrared (NIR-II) window provides advantages including high resolution and fast feedback. However, the reported molecular dyes are hampered by limited blood circulation time (~ 5–60 min) and short absorption and emission wavelength, which impede the accurate long-term monitoring. Here, we report a NIR-II molecule (LZ-1105) with absorption and emission beyond 1000 nm. Thanks to the long blood circulation time (half-life of 3.2 h), the fluorophore is used for continuous real-time monitoring of dynamic vascular processes, including ischemic reperfusion in hindlimbs, thrombolysis in carotid artery and opening and recovery of the blood brain barrier (BBB). LZ-1105 provides an approach for researchers to assess vessel dysfunction due to the long excitation and emission wavelength and long-term blood circulation properties. Optical bioimaging in the second near-infrared (NIR-II, 1000–1700 nm) window exhibits abundant advantages. Here the authors report an organic NIR-II molecule with long blood circulation half-life time for continuous real-time monitoring of dynamic vascular processes.